CT colonography interpretation times: effect of reader experience, fatigue, and scan findings in a multi-centre setting. - Burling, D; Halligan, S; Altman, D; Atkin, W; Bartram, C; Fenlon, H; Laghi, A; Stoker, J; Taylor, S; Frost, R; Dessey, G; De Villiers, M; et al. (2006)
Our purpose was to assess the effect of reader experience, fatigue, and scan findings on interpretation time for CT colonography. Nine radiologists (experienced in CT colonography); nine radiologists and ten technicians (both groups trained using 50 validated examinations) read 40 cases (50% abnormal) under controlled conditions. Individual interpretation times for each case were recorded, and differences between groups determined. Multi-level linear regression was used to investigate effect of scan category (normal or abnormal) and observer fatigue on interpretation times. Experienced radiologists (mean time 10.9 min, SD 5.2) reported significantly faster than less experienced radiologists and technicians; odds ratios of reporting times 1.4 (CI 1.1, 1.8) and 1.6 (1.3, 2.0), respectively (P